Looking beyond left ventricular ejection fraction – a new multiparametric CMR score to refine the prognostic assessment of HF patients. (3rd October 2022) - Lopes Da Cunha, G J; Rocha, B; Sousa, J; Maltes, S; Brizido, C; Strong, C; Guerreiro, S; Abecasis, J; Andrade, M J; Aguiar, C; Saraiva, C; Freitas, P; et al.
Abstract: Background: Cardiac magnetic resonance (CMR) is recommended in Heart Failure (HF) to assess myocardial structure and function. Recently, the quantification of pulmonary congestion and skeletal muscle mass using CMR have been shown to predict adverse events in HF, but a tool integrating this information is currently unavailable. The purpose of this study was to develop and test a new multiparametric CMR-derived score. Methods: We conducted a single-center retrospective study of consecutive HF patients with left ventricular ejection fraction (LVEF) <50% who underwent CMR. Several CMR parameters with known prognostic value were assessed, including: LVEF, Lung Water Density (LWD), Pectoralis Major Muscle (PMM) area, and presence of Late Gadolinium Enhancement. PMM area was outlined at the level of the carina – Figure 1A, B – and LWD was defined as the lung-to-liver signal ratio multiplied by 0.7, as previously described. Both parameters were measured in standard HASTE images - Figure 1C. The primary endpoint was a composite of all-cause death or HF hospitalization. Using the Cox regression Hazard Ratios of designated variables, a risk score was developed. Results: Overall, 436 patients were included. During a median follow-up of 27 (17–37) months, 43 (9.9%) patients died and 57 (13.2%) had at least one hospitalization for HF. LVEF, LWD and PMM were independent predictors of the primary endpoint and were included in the CMR-HF score – Figure 2. The annual rate of events increased from 4.7 to 7.5 and 20.0% from lowest to highest tertile of the score. Roughly half of the events (54%) occurred in patients in the highest tertile of the CMR-HF score. In multivariate analysis, the new score independently predicted the primary endpoint (HR per 5 points: 1.54; 95% CI: 1.21–1.97; p<0.001) even after adjustment for age, body mass index, NYHA class, NT-proBNP, estimated glomerular filtration rate, presence of implantable cardioverter-defibrillator, and ischemic etiology. Conclusions: This novel multidimensional CMR-HF score, combining easily obtainable data on left ventricular pump failure, lung congestion and muscular wasting, is a promising tool identifying HF patients with an LVEF <50% at higher risk of death or HF hospitalization. Funding Acknowledgement: Type of funding sources: None.